2019
DOI: 10.1080/09500693.2019.1615656
|View full text |Cite
|
Sign up to set email alerts
|

From science teacher to ‘teacher scientist’: exploring the experiences of research-active science teachers in the UK

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 26 publications
4
19
1
1
Order By: Relevance
“…The interviews showed that some teachers identified particularly strongly as scientists, where being involved in the co-production of knowledge with their students was a great opportunity to reinforce their disciplinary interests and identity, as well as developing networks beyond their school. This corroborates earlier work on the 'teacher scientist' (Rushton & Reiss, 2019). These teachers tended to emphasise the intellectual and professional socialisation forms of support (Thiry & Laursen, 2011) that they offer through their mentoring in supporting the next generation of scientists, but also by actively doing science themselves.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The interviews showed that some teachers identified particularly strongly as scientists, where being involved in the co-production of knowledge with their students was a great opportunity to reinforce their disciplinary interests and identity, as well as developing networks beyond their school. This corroborates earlier work on the 'teacher scientist' (Rushton & Reiss, 2019). These teachers tended to emphasise the intellectual and professional socialisation forms of support (Thiry & Laursen, 2011) that they offer through their mentoring in supporting the next generation of scientists, but also by actively doing science themselves.…”
Section: Discussionsupporting
confidence: 82%
“…Mentoring can support professional development and enhance teacher motivation through being provided with a new challenge hand in hand with developing new disciplinary knowledge. In turn, teachers become more confident and outward looking through the development of professional networking, identifying as 'teacher scientists' (Rushton & Reiss, 2019) and 'teacher mentors'.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations